Gemology and Geochemistry of Staurolites from the Casa Nova Region, Brazil - Gomes de Oliveira, Isaac; Pinto Bezerra, Isabelle; Ravielly dos Santos, Breno; De Sousa Silva, Larissa; Leal Neto, Antonio; dos Santos, Lucilene; Falcão de Oliveira Neri, Tereza (Anuário do Instituto de Geociências, 2024)
The properties of minerals used as gemstones could help or even reveal new aspects about the geological evolution of the region where a mineral was found. The objective of this study was the gemological characterization and acquisition of chemical data on staurolites from the city of Casa Nova (Bahia, Brazil). The gemological data are within the normal range for the staurolite mineral, except for the absence of pleochroism, above-average densities in two specimens, and a rare color (intense red) in a sample. The intrinsic part of these gems is in possible correlations involving their properties, such as: color, refractive index, birefringence, relative density, and the amounts of FeO in the samples. The geochemistry of these samples is unusual; FeO and MgO appear in considerably above-average quantities, and Al2O3 is up to 8% below average; the presence of CaO is also rare. Therefore, staurolites from Casa Nova (Bahia) have the potential to be used as gemstones, and their geochemistry combined with the gemology of these samples is a great indication for further studies.